Lever-press duration as a measure of frustration in sucrose and drug reinforcement - Vasquez, Tileena E. S.; McAuley, Ryan J.; Gupta, Nikita S.; Koshy, Shyny; Marmol-Contreras, Yorkiris; Green, Thomas A. (Psychopharmacology, 2021)
Rationale Currently there is little research into the role of frustration in substance use disorders despite research showing that frustration tolerance in humans is associated with a lower likelihood of developing substance use problems, better outcomes in recovery, and fewer relapses. Objective In order to address this need, our studies use a rat model to focus on frustration-related behavior in natural reward and addiction-related behavioral procedures. Frustration is defined as when a subject is unable to achieve a reinforcer, receives less of a reinforcer than anticipated, or has to work harder to achieve a reinforcer. Results In these studies, bar-press durations increase when rats are in a state of frustration during self-administration of sucrose, fentanyl, or cocaine. Conclusions These data also show that average bar-press durations do not correlate with the number of bar presses, meaning that press duration is an independent measurement that represents a behavioral construct distinct from craving, which is typically measured with number of bar presses. Essentially, these results support that bar press durations can be used as a real-time measure of frustration as a 4th major facet of addiction-related behavior, adding to craving, impulsivity, and habit.